Salmonella spp. isoladas em abatedouro frigorífico de suínos: resistência a sanitizantes e antimicrobianos - Quadros, Caroline Luneli de (2018)
Brazil is the fourth largest pork producer and exporter of the world, besides, the swine productive chain represents a very important economic base for the country. However, the sector faces difficulties like detecting bacteria from the Salmonella gender in the swine herd and slaughterhouses, because this bacteria is one of the most important agent related to foodborne diseases and pork meat has been associated as an important food vehicle. To know the major risk points of contamination by Salmonella spp. at the different slaughtering steps is crucial to properly control the process, as well as the correct realization of cleaning and sanitizing, essential to control the environment microorganisms, all of these with the final intention to produce pork meat products safe for consumption. The dissemination of bacterial resistance to antimicrobials and sanitizers has been concerning authorities worldwide, at animal and human health level. In this context, it was identified the presence of Salmonella spp. at the different steps in a swine slaughterhouse and evaluated the action of sanitizers (peracetic acid 0,5% e 1%, and quaternary ammonium 0,5%) and antimicrobials (enrofloxacin 5mcg, florfenicol 30mcg, amoxicillin 10mcg, cephaclor 30mcg, lincomycin 2mcg, azithromycin 15 mcg, doxycycline 30mcg and chloramphenicol 30mcg) against these isolates. It was evaluated 150 samples, 60 from the lairage floor (environment samples) and 90 from the carcass surface at the studied slaughterhouse. From de environment samples, 38% (23/60) were positive for Salmonella spp., which 53% (16/30) were from before de cleaning process and 23% (7/30) after de cleaning process. About the carcass sampling, 21% (19/90) were positive for Salmonella spp. The exsanguination stage was the most positive point (46,7%), followed by the final carcass wash (16,7%), and there was no isolation at all after the carcass cooling. About the sanitizers, the peracetic acid at both concentration was efficient at all exposure times, however de quaternary ammonium 0,5% was efficient at all exposure times with 26,9% of the isolates, 5 (19,2%) were resistant with 5 minutes of exposure, 6 (23%) were resistant up to 10 minutes of exposure and 8 (30,7%) were resistant to all the exposure times. For the antimicrobial test, 48% of the samples were multiresistant. Lincomycin (100%), amoxicillin (80%) and chloramphenicol (40%) had the highest resistance level. All the samples were sensitive to enrofloxacin. Due to the difficulty to control Salmonella at the swine herds, it makes indispensable to maintain the control of the slaughter operations, cleaning and disinfection procedures, as also employees qualification, with the objective of reduce the presence of Salmonella spp. at acceptable levels or eliminate it, providing safe pork meat products. Furthermore, monitoring de sensibility profile of the most used antimicrobial products at the swine chain is fundamental to take decisions about the correct use of these medications.